Towards a Structured Obesity Policy in Indonesia: Lessons from the Implementation of Metabo Law in Japan - Anindya Naila Sabahat; Dumilah Ayuningtyas (Eduvest - Journal of Universal Studies, 2025)
Obesity is a growing global public health challenge, especially in developing countries. In Indonesia, the prevalence of adult obesity has reached 23.4%, but the control policy remains limited to a promotive-preventive approach without binding regulations. In contrast, Japan implements a Metabo Law policy that combines mandatory screening, clear anthropometric parameters, and a health insurance-based institutional incentive system. This research aims to analyze the success of the Metabo Law policy in Japan and evaluate its potential adoption or adaptation in the context of Indonesia and other developing countries. This research used a qualitative literature review approach by examining obesity policies in Japan, India, Thailand, the Philippines, Brazil, and Indonesia. The analysis was carried out thematically based on scope, intervention mechanisms, financing, institutional structure, and socio-cultural context. The Metabo Law succeeded in reducing the prevalence of metabolic syndrome through a regulative and population-based approach. Compared to developing countries, Japan's policies excel in terms of national coverage, institutional accountability, and funding sustainability. However, the success of the Metabo Law was greatly influenced by the context of Japanese collectivism and an integrated national health system, which are not yet fully present in developing countries. The adoption of policies such as the Metabo Law needs to be contextually adjusted. Indonesia can draw inspiration from such policy structures and mechanisms, especially in building a national screening system, strengthening regulations, and developing institutional incentives.